FRANZH Enterprise - Robert, Herold; Suasan, Raynolson; John, Farleys Edpieson; Jaimairi, Nasaruddin; Jun Alias, Mohd Ruzaini; Abdul Mumen, Abdul Muin (2016)
The name of our company is FRANZH Enterprise. FRANZH is a business that provides product to the customer on the behalf of our own company. We made new product to satisfy our customer needs. The nature of our business is partnership. Our main office is located at Bandar Prima Batu 4 Sandakan. We expect to start up our business on 1st January 2017. With the modal and idea provided by each partner, we decided to kick start our business. The future prospects of our business are people around Malaysia especially those who are outdoor sport freak. This is because, based on observation on Bandar Prima there are many people who like to bought outdoor outlet and sport kind of things. We are prospecting to increase 2 % and 3 % sales of our business on second and third year respectively.